Strategi Penanggulangan Stunting Melalui Peningkatan Pengetahuan Pasangan Usia Subur Tentang Bahaya Stunting di Desa Oringbele Kecamatan Witihama Kabupaten Flores Timur - Dai, Maria Yoana Ina; Boro, Veronika I.A. (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
One of the primary causes of stunting is the lack of public knowledge and awareness about stunting prevention, particularly among couples of childbearing age who play a crucial role in preventing stunting. Adequate knowledge about healthy eating patterns, exclusive breastfeeding, the importance of pregnancy control, and child immunization is still lacking among this group. This community service activity aims to: (1) Increase the knowledge and awareness of couples of childbearing age about stunting prevention in Oringbele Village; (2) Encourage the application of healthy behaviors during pregnancy preparation and childcare; and (3) Support government efforts to reduce stunting rates in Indonesia. The service activities utilized counseling and lecture methods, supported by PowerPoint slides and leaflets that provided explanations on the definition, causes, negative impacts, risk factors, and prevention strategies of stunting. The results showed a significant improvement in the knowledge of couples of childbearing age across all dimensions of the questionnaire, including the definition, symptoms, causes, dangers, and prevention of stunting. Thus, it can be concluded that the stunting prevention counseling activities in Oringbele Village were successful, as evidenced by the increased awareness and healthy behaviors among the participants, contributing to the reduction of stunting incidents from the outset.